SAILING TRACK DESIGNING OF FISHING VESSEL “KM. UMA 002”, PT UMA NIAN NEPA MAUMERE - Keytimu, Atanasius Merdin Andi Odang; Pale, Christofel Oktavianus Nobel; Tei, Maria Theresia Du’a (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Navigation in sailing is a crucial aspect that determines the safety and efficiency of a vessel’s journey, especially for fishing vessels operating in open waters. This study aims to design and develop an optimal sailing track for KM Uma 002, a fishing vessel owned by PT Uma Nian Nepa operating in the waters of the Flores Sea. The track design considers environmental factors such as currents, weather, sea depth, and vessel characteristics to enhance travel time efficiency and operational safety. The research methodology used is an applied approach with primary data collection through direct observations of the ship’s sailing route using nautical chart No. 116, interviews with crew members, and navigation analysis. Secondary data were obtained from literature on voyage route planning and the latest navigation technology. The track design includes determining waypoint coordinates, plotting the True Course (HS), calculating the total distance to travel (Distance to Go/DTG), and estimating the time of arrival (ETA). The results indicate that the outer route is safer and more efficient than the inner route, which poses navigation challenges due to narrow waters and numerous coral reefs. Based on the analysis, the journey from the fishing base to the fishing ground at a speed of 6 knots has an estimated travel time of approximately 12.25 hours. With an optimized navigation design, the vessel's operational efficiency is expected to improve while minimizing the risk of maritime accidents. Key words: fishing vessels, KM. Uma 002, navigation, sailing tracks